On the nature of suppes-sen choice functions in an aggregative growth model - Ram Sewak Dubey; Tapan Mitra (Cornell University, Center for Analytical Economics (CAE), 2010)
This paper investigates the nature of paths in the standard neoclassical aggregative model of economic growth that are maximal according to the Suppes-Sen grading principle. This is accomplished by relating such paths to paths which are utilitarian maximal when an increasing (but not necessarily concave) utility function evaluates each period's consumption. An example is presented in which an explicit form of a consumption function is described, which generates only Suppes-Sen maximal paths. This consumption function is shown to generate consumption cycles, and violate the Pigou-Dalton transfer principle.
Keywords: D60; D70; D90; 330; Suppes-Sen Grading Principle; Utilitarian Maximality; Non-concave utility function; Consumption Cycles; Pigou-Dalton Transfer Principle; Eigeninteresse; Zeitpräferenz; Utilitarismus; Wachstumstheorie; Neoklassik; Theorie